YAP Activation and Implications in Patients and a Mouse Model of Biliary Atresia - Zheng, Chao; Luo, Jiaqian; Yang, Yifan; Dong, Rui; Yu, Fa-Xing; Zheng, Shan (Frontiers in Pediatrics, 2021)
Background and Aim: Biliary atresia (BA), an inflammatory destruction of the bile ducts, leads to liver fibrosis in infants and accounts for half of cases undergoing pediatric liver transplantation. Yes-associated protein (YAP), an effector of the Hippo signaling pathway, is critical in maintaining identities of bile ductal cells. Here, we evaluated the expression of YAP and YAP target genes in BA livers and a rhesus rotavirus (RRV)-induced BA mice model. Methods: Liver specimens collected from 200 BA patients were compared with that in 30 non-BA patients. Model mice liver tissues were also collected. The expression of YAP and YAP target genes were measured by transfection, RNA-seq, immunohistochemistry, immunoblot and quantitative PCR. Masson’s trichrome staining and the BARC system were utilized to score liver fibrosis status. Results: The expression of YAP is elevated and positively correlated with fibrosis in BA livers. Moreover, ANKRD1, which is identified as the target gene of YAP, is also highly expressed in BA livers. Consistent with clinical data, YAP and ANKRD1 are significantly upregulated in RRV-induced BA mouse model. Conclusions: YAP expression is closely correlated with the bile duct hyperplasia and liver fibrosis, and may could be served as an indicator for liver fibrosis and BA progression. This study underscores the involvement of the Hippo signaling pathway in the development of BA, and the increased expression of YAP causing the up-regulation of downstream ANKRD1, which may be related to bile duct hyperplasia in BA. This provides a new direction for more in-depth exploration of the etiology and pathogenesis of biliary atresia.